Influence of wax content on the electrical, thermal and tribological behaviour of a polyamide 6/graphite composite - ESMER, KADİR (WALTER DE GRUYTER GMBH, 2016)
In this study, the influence of wax content on the electrical, thermal and tribological properties of a polyamide 6 composite filled with 15% wt. graphite was investigated. The wax filler contents of the composite were by 2, 4 and 6 wt.%. Characterisation of the composites was obtained using a Fourier transform infrared spectroscopy test. Electrical performance tests were carried out, and the dielectric real values (epsilon') and imaginary values (epsilon '') were recorded. Thermal differential scanning calorimetry tests were carried out, and the glassy and melting temperatures of the composite materials were recorded. Furthermore, tribological tests were carried out and the friction coefficient and wear rate of the composites were recorded. The results show that the increase in wax content led to the increase in the permittivity values (epsilon' and epsilon '') of the composites. The increase in wax content also led to the decrease in the friction coefficient and wear rates of the composite materials. Furthermore, the glassy and melting temperatures of the composite materials showed a sensitivity to the wax content. Finally, it is concluded that optimum properties, in total, were obtained in the composite filled with 6 wt.% wax.
Keywords: composite; electrical; polyamide 6; thermal wear; wax; POLYMER COMPOSITES; SLIDING WEAR; GRAPHITE; NANOCOMPOSITES; CONDUCTIVITY; NANOPLATELETS; POLYETHYLENE